SISTEM INFORMASI PENYEWAAN KONTRAKAN (PETRA) DI LINGKUNGAN BUARAN BERBASIS WEBSITE - Heril Worang; Malik Al Asytar; Saghifa Fitriana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Abstracts - The use of the current infromation system is very important, especially in the field of property businesses such as rental contracts. In this case the process that still uses manual means, namely the delivery of information using the medium of a piece of paper or with a banner attached to the wall seems less effective and efficient, with the use of information systems, businesses or businesses can survive and develop for the better, while those who still use manual means will affect over time with the development of technology. Through this website-based rental that aims to minimize time or more efficiently and the rental owner can promote his residence, in addition, the tenant can also be facilitated in terms of knowing the details of prices, ordering and rental locations that are ready to be inhabited as needed. Based on the results of this research, the establishment of a website-based rental information system (PETRA) that is expected to facilitate the process of processing data for tenants and renters. Keywords: Lease, Rent, Information System, Website